EFFECTIVENESS OF WORKSHOPS IN SUPPORTING THE SMOOTH RUNNING OF SHIPPING NAVIGATION AID FACILITIES IN THE WORKING AREA OF THE TYPE A CLASS I BITUNG NAVIGATION DISTRICT - Adarto Adrian Sasongke (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the effectiveness of workshop operations in supporting the smooth operation of Navigation Aids (SBNP) in the working area of Bitung Class I Type A Navigation District and to identify factors that influence its effectiveness. This study uses a qualitative approach with a focus on analyzing the effectiveness of public organizations through input, process, output, and outcome aspects. Data collection was conducted through interviews, observations, and documentation of related parties in Bitung Class I Type A Navigation District. Data analysis was conducted descriptively by interpreting the relationship between technical, administrative, and managerial aspects in workshop operations. The results of the study indicate that the effectiveness of workshops in supporting the smooth operation of SBNP has not been running optimally. The main obstacles include limited competence and number of technical human resources, inadequate work facilities and equipment, limited operational budget, and suboptimal coordination and preventive maintenance systems. Nevertheless, workshops still have a strategic role in supporting the readiness of navigation facilities and shipping safety in the working area of Bitung Class I Navigation District. This study concludes that increasing workshop effectiveness requires strengthening human resource capacity, modernizing supporting facilities, increasing budget allocation, and improving the coordination system and operational management on an ongoing basis.